2021
DOI: 10.3390/molecules26061742
|View full text |Cite
|
Sign up to set email alerts
|

Fast Screening of Biomembrane-Permeable Compounds in Herbal Medicines Using Bubble-Generating Magnetic Liposomes Coupled with LC–MS

Abstract: A novel strategy based on the use of bionic membrane camouflaged magnetic particles and LC–MS was developed to quickly screen the biomembrane-permeable compounds in herbal medicines. The bionic membrane was constructed by bubble-generating magnetic liposomes loaded with NH4HCO3 (BMLs). The lipid bilayer structure of the liposomes enabled BMLs to capture biomembrane-permeable compounds from a herbal extract. The BMLs carrying the compounds were then separated from the extract by a magnetic field. Upon heat trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There are typically two methods for connecting the biomembrane with the carrier material. Biomembrane wraps nano‐ and micro‐materials such as MNPs (Gu et al, 2021) and silica microspheres (He et al, 2018) as shown in Figure 1(a). Figure 1(b) depicts another technique.…”
Section: Supported Materials Of Biomembranementioning
confidence: 99%
“…There are typically two methods for connecting the biomembrane with the carrier material. Biomembrane wraps nano‐ and micro‐materials such as MNPs (Gu et al, 2021) and silica microspheres (He et al, 2018) as shown in Figure 1(a). Figure 1(b) depicts another technique.…”
Section: Supported Materials Of Biomembranementioning
confidence: 99%
“…Therefore, it is very important to develop an effective, time-saving, and reliable method for the screening of small-molecule inhibitors of A β from natural medicines. To date, several screening methods reported, including cell membrane chromatography (CMC) 25 , network pharmacology and molecular docking 26 , affinity ultrafiltration with drug targets of interest coupled to high-performance liquid chromatography−mass spectrometry (AUF−HPLC−MS/MS) 27 , bubble-generating magnetic liposomes coupled with liquid chromatography−mass spectrometry (LC−MS) 28 , etc. In general, most of them are developed based the application of advanced analytical instruments, such as HPLC, MS, and nuclear magnetic resonance (NMR) 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%